Outcomes of dorsal nasal augmentation using costochondral graft - Amna Kifayatullah; Mamoon Rashid; Saad Ur Rehman; Ibrahim Khan (Journal of the Pakistan Medical Association)
Objective: To assess functional and aesthetic outcomes in patients having undergone dorsal nasal augmentation with costochondral graft in a tertiary care setting.